Dynamic perspective on the function of thermoresponsive nanopores from in situ AFM and ATR-IR investigations - Popa, Ana Maria; Angeloni, Silvia; Bürgi, Thomas; Hubbell, Jeffrey A.; Heinzelmann, Harry; Pugin, Raphaël (Langmuir, 2010)
This article describes the morphological and chemical characterization of stimuli-responsive functionalized silicon surfaces provided in parallel by atomic force spectroscopy (AFM) and Fourier transform infrared spectroscopy (FT-IR) enhanced by the single-beam sample reference attenuated total reflection method (SBSR-ATR). The stimuli-responsive behavior of the surfaces was obtained by grafting-to in melt carboxyl-terminated poly-N-isopropylacryl amides (PNIPAAM) with different degree of polymerization (DP) on epoxide-functionalized silicon substrates. The unprecedented real time and in situ physicochemical insight into the temperature-triggered response of the densely packed superficial brushes allowed for the selection of a PNIPAAM with a specific DP as a suitable polymer for the fabrication of silicon membranes exhibiting switchable nanopores. The fabrication process combines the manufacture of nanoporous silicon surfaces and their subsequent chemical functionalization by the grafting-to in melt of the selected polymer. Then, relevant information was obtained in what concerns the chemical modifications behind the topographical changes that drive the functioning of PNIPAAM-based hybrid nanovalves as well as the timescale on which the opening and closing of the nanopores occur.